Industry clusters and Irish indigenous manufacturing: limits of the Porter view - O'Malley, Eoin; Van Egeraat, Chris (Economic & Social Studies, 2000)
Studies by Porter (1990) and others find that competitive and successful industries usually occur in the form of clusters of industries which are linked together through vertical or horizontal relationships. This paper assesses whether the sectors of Irish indigenous industry which look most competitive and successful form such clusters. We also consider whether the recent growth performance of Irish indigenous industry has been linked to clustering and to the sectors identified as relatively strong. It is concluded that there is only limited or qualified evidence of Porter-type clusters in Irish indigenous industry, and that there is no clear association between the occurrence of such clusters, or established strong sectors, and the growth performance of indigenous manufacturing. We also comment on policy implications.
Keywords: Industry clusters; Manufacturing sector; Ireland; Clusters